PENGARUH KESADARAN, PENGETAHUAN, PELAYANAN FISKUS DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KOTA SURAKARTA - Sukma Trihana; Ismunawan Ismunawan (Jurnal Inovasi Penelitian, 2022)
The government in current years has taken various methods to increase country sales, particularly tax income. every year the variety of tax income goals will increase due to the need for country spending which maintains to growth each year. Taxes are received from network contributions, while paying taxes, the country does now not offer direct compensation. Taxes are coercive and the proceeds need to be used for country wishes. This have a look at goals to look at the effect of taxpayer focus, taxpayer information, tax provider services and tax sanctions on character taxpayer compliance because of the impact of covid-19. This research have become performed on character taxpayers in the town of Surakarta, the sort of records used modified into quantitative information. The statistics supply uses number one information. The populace within the take a look at become 142,210 character taxpayers. The variables on this have a observe are independent variables, especially taxpayer cognizance (X1) Taxpayer knowledge (X2) financial provider (X3) and Tax Sanctions (X4), on the same time because the structured variable is person taxpayer compliance (Y) The sample used is a hundred respondents the use of Slovin's additives. gathering facts the usage of a questionnaire. Assumption check using take a look at: multicollinearity, heteroscedasticity and normality. The records evaluation technique used more than one linear regression analysis, t test, F take a look at and R2 test with the assist of SPSS version 19 for home home windows. The results of the have a look at know-how that: 1) taxpayer consciousness has a huge impact on man or woman taxpayer compliance; 2) Taxpayer knowledge has no considerable impact on individual taxpayer compliance; 3) tax sanctions have a big effect on man or woman taxpayer compliance; and 4) tax provider services have a large impact on character taxpayer compliance.